Length at first maturity of cobia Rachycentron canadum (Linnaeus, 1766) from north-west coast of India - Sajeevan, M.K.; Madhusoodana Kurup, B. (Indian Journal of Fisheries, 2017)
The length at first maturity of cobia Rachycentron canadum (Linnaeus, 1766) was estimated from 292 specimens collected during exploratory surveys along the north-west coast of India and from fish landing centres in Mumbai, Maharashtra. Length and age at first maturity of male and female were estimated as 63 and 70 cm and 1.5 and 1.75 years respectively.